(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper offers a comprehensive analysis of the Self-Help Group (SHG) bank linkage program’s progress in Andhra Pradesh from 2016-17 to 2020-21, highlighting significant growth in SHG savings, bank loans, and outstanding loan amounts. Based on data from the ’Reports of the Status of Microfinance in India’ published by NABARD, Mumbai, the study underscores the positive impact of SHGs on financial inclusion and community-driven savings in the region. While fluctuations are observed in bank loans disbursed and the number of SHGs with outstanding loans, Andhra Pradesh consistently maintains a notable presence at the national level. The paper advocates for enhanced monitoring and evaluation, financial literacy, capacity building, adaptation to economic changes, government collaboration, technology integration, risk mitigation, social capital promotion, and community engagement to ensure the sustained growth of savings, loan disbursements, and SHGs’ impact on financial inclusion in Andhra Pradesh.